2018
DOI: 10.1515/ncrs-2017-0363
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of phthalazin-1(2H)-one, C8H6N2O1

Abstract: C8H6N2O1, monoclinic, P21/c (no. 14), a = 8.6277(17) Å, b = 13.134(3) Å, c = 13.062(5) Å, β = 110.54(3)°, V = 1386.0(7) Å3, Z = 8, Rgt(F) = 0.0512, wRref(F2) = 0.1581, T = 293(2) K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…[3]. Yun-Chen et al synthesized nitrogen heterocyclic compound Phthalazin-1(2H)-one and reported its crystal structure [4]. Yathirajan et al obtained phthalazin-1(2H)-one-picric acid using cocrystallisation methods and reported its structural details [5].…”
Section: Introductionmentioning
confidence: 99%
“…[3]. Yun-Chen et al synthesized nitrogen heterocyclic compound Phthalazin-1(2H)-one and reported its crystal structure [4]. Yathirajan et al obtained phthalazin-1(2H)-one-picric acid using cocrystallisation methods and reported its structural details [5].…”
Section: Introductionmentioning
confidence: 99%